Parliament and parliament committees at work: inside view - Gadhok, D. N. (New Delhi, 2000)
This book about is described in detail the composition and working fo major problems, both human and systemic, that inhibit their performance. For instance, past experience shows that the Chairman to the Public Account Committee.
Keywords: Parliament - India